ACTIVE EXCHANGE RATE POLICY AS INSTRUMENT OF SUPPORT FOR ECONOMY COMPETITIVENESS ON THE EXAMPLE OF CHINA - Żuchowska, Dorota (Ekonomia i Prawo. Economics and Law, 2013)
An active exchange rate policy is used to implement the economic goals set by the monetary authorities. One of them may be to promote the competitiveness of the economy. In recent years, China is an interesting example of an active exchange rate policy. Its current position on the world market is due to the export-oriented exchange rate policy. The article aims at analysing China’s exchange rate policy (decision of the Chinese monetary authorities referring to modification of the exchange rate policy and shaping nominal and real exchange rates of the renminbi, the level of foreign currency reserves) and its impact on the competitive position of the country in the international arena.